2020
DOI: 10.1111/ijlh.13195
|View full text |Cite
|
Sign up to set email alerts
|

Testing for antiphospholipid antibodies: Advances and best practices

Abstract: The diagnosis of antiphospholipid syndrome (APS) relies on the detection of circulating antiphospholipid antibodies (aPL). Currently, lupus anticoagulant (LAC), anticardiolipin (aCL), and antibeta2-glycoprotein I antibodies (aβ2GPI) IgG or IgM are included as laboratory criteria if persistently present. Progress has been made on the standardization of tests as guidelines on LAC testing and immunological assays for aCL and aβ2GPI are published. However, LAC measurement remains a complicated procedure with many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 73 publications
0
43
2
Order By: Relevance
“…Some studies have found a high prevalence of aPL [ 6 •, 18 , 23 , 37 , 43 , 57 ] while others found a low prevalence and this could be linked to disease severity [ 19 , 24 , 26 , 35 •, 42 , 45 , 55 ]. Xiao et al found aPL in 31 out of 66 patients requiring ICU admission but not in patients with noncritical conditions [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found a high prevalence of aPL [ 6 •, 18 , 23 , 37 , 43 , 57 ] while others found a low prevalence and this could be linked to disease severity [ 19 , 24 , 26 , 35 •, 42 , 45 , 55 ]. Xiao et al found aPL in 31 out of 66 patients requiring ICU admission but not in patients with noncritical conditions [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main reason is probably linked to aPL tests and the interpretation of the results. Assays may be affected by several analytical factors, including methodological issues due to the heterogeneity of aPL, different tests from one laboratory to another, and pre-analytical factors due to the clinical condition of the patient in whom the assay is performed [ 57 ]. In particular inflammation may cause false positive determination of LA [ 66 – 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The general approach is to test the anti-β 2 GPI and the anti-CL antibodies both for IgG and IgM autoantibodies, and it was concluded that there is no strong evidence suggesting that IgA isotypes provide additional information except in rare cases. [33][34][35] Undoubtedly, the strongest predictor is IgG, and more recent data also question the general usefulness of the IgM aPLs 36,37 and on the other hand there is also evidence that the anti-β 2 GPI IgA significantly adds to the evaluation of thrombotic risk (e.g., in SLE). 38 To avoid transient autoantibodies, measurements should be performed two times, 12 weeks apart.…”
Section: Methods For Measuring Antiphospholipid Autoantibody Concentrationsmentioning
confidence: 99%
“…The significance of aCL IgA for the development of thrombotic complications has also been of much interest recently [47]. Using CLIA (cut-off recommended by the manufacturer >20 CU), Liu et al detected aCL IgA in 192 samples of APS in 42%, in 90 samples of seronegative APS (SN-APS) in 12%, and in healthy donors in 0% [24].…”
Section: Anti-cardiolipin Igamentioning
confidence: 99%
“…The LA results are interpreted according to ISTH SSC as positive/negative based on the normalized ratio (NR) calculation (NR = patient/polled normal plasma (PNP)) [69]. With regard to the use of different analyzers and reagents, each laboratory should determine its own cut-off for LA (99th percentile) by measuring ideally 120 (minimally 40) healthy controls [47,70,71]. Cohen et al [72] carried out a survey in 575 laboratories by means of a "Lupus Program," the External quality Control of diagnostic Assay and Test Foundation (ECAT).…”
Section: Antibodies Against Phospholipid Antigensmentioning
confidence: 99%